2013
DOI: 10.1371/journal.pone.0074224
|View full text |Cite
|
Sign up to set email alerts
|

Isn’t it ironic? Neural Correlates of Irony Comprehension in Schizophrenia

Abstract: Ironic remarks are frequent in everyday language and represent an important form of social cognition. Increasing evidence indicates a deficit in comprehension in schizophrenia. Several models for defective comprehension have been proposed, including possible roles of the medial prefrontal lobe, default mode network, inferior frontal gyri, mirror neurons, right cerebral hemisphere and a possible mediating role of schizotypal personality traits. We investigated the neural correlates of irony comprehension in sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 99 publications
5
55
2
1
Order By: Relevance
“…27,97,98 Besides odd speech and thought disorder, individuals with elevated schizotypy show differences in correct production and interpretation of nonliteral language such as metaphors, 99 irony, 80,99,100 fauxpas, 101 and proverbs, 102 similar to schizophrenia and autism. While nonliteral language comprehension problems seem correlated with schizotypy across the spectrum, 80,102 the association in nonclinical schizotypy is subtle 103 or even controversial, 100,104 but still detectable on the neural level. 105 A number of mechanisms may contribute to these deficits, 106 including semantic association differences, [107][108][109] aberrant semantic priming mechanisms, 106 and inadequate context integration.…”
Section: Language Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…27,97,98 Besides odd speech and thought disorder, individuals with elevated schizotypy show differences in correct production and interpretation of nonliteral language such as metaphors, 99 irony, 80,99,100 fauxpas, 101 and proverbs, 102 similar to schizophrenia and autism. While nonliteral language comprehension problems seem correlated with schizotypy across the spectrum, 80,102 the association in nonclinical schizotypy is subtle 103 or even controversial, 100,104 but still detectable on the neural level. 105 A number of mechanisms may contribute to these deficits, 106 including semantic association differences, [107][108][109] aberrant semantic priming mechanisms, 106 and inadequate context integration.…”
Section: Language Productionmentioning
confidence: 99%
“…78 Neuroimaging evidence for these aberrant laterality patterns have been published recently. 79,80 In summary, there is plenty of evidence showing that attention (selection and inhibition), WM and memory is reduced in schizotypy. There is evidence for both deficits in individuals with psychometrically identified schizotypy relative to individuals with low levels of schizotypal traits, as well as evidence for associations between specific deficits and specific schizotypal dimensions.…”
Section: Attention and Memorymentioning
confidence: 99%
See 1 more Smart Citation
“…The neural bases of higher order language perception abilities have also been examined. For example, linguistic irony, which is a metacognitive and social cognitive function, is reported to be disrupted in many psychiatric conditions, including schizophrenia and autism [Rapp et al, ; Rapp et al, ; Varga et al, ]. These studies have indicated involvement of posterior medial prefrontal and right temporal regions in the defective irony comprehension in schizophrenia, together with an association between activation in these regions and schizotypal personality traits [Rapp et al, ].…”
Section: Neuroimaging Of Languagementioning
confidence: 99%
“…The condition seems to be more complicated in schizophrenic patients for they have abnormal lateralization (Kircher, Leube, Erb, Grodd, & Rapp, 2007;Mashal, Vishne, Laor, & Titone, 2013). Rapp et al (2013) carried out an experiment in which 15 SPs and 15 healthy participants were involved and they were all female. The participants were asked to read irony and their brain activation had been recorded.…”
Section: Lateralizationmentioning
confidence: 99%